Familienwissenschaft als Praxiswissenschaft im Interesse einer lebensfreundlichen Gesellschaft (European Journal of Mental Health, 2015)
Family Science as a Practical Science in the Service of a Life-Friendly Society: The family is considered to be an essential institution of generativity and generative socialisation in a wide variety of societies. No single discipline can examine all the conditions and possibilities of how families perform that task. Approximately a dozen different empirical, hermeneutic and normative sciences explore family-related issues with the help of different methods and approaches. However, an interdisciplinary convergence of these sciences still seems quite far off. In the meantime, we recommend that the various disciplines work together, as a kind of teaching and learning community with the aim of somehow coordinating their research on the conditions of founding a family, the diverse roles and stresses of family members and on long-term care provided in the context of ageing societies, to adopt common options that support late modern families and their members.